2018
DOI: 10.1007/s10120-018-0892-0
|View full text |Cite
|
Sign up to set email alerts
|

CRP/prealbumin, a novel inflammatory index for predicting recurrence after radical resection in gastric cancer patients: post hoc analysis of a randomized phase III trial

Abstract: Background Serum prealbumin (PALB) can predict the prognosis of patients with gastric cancer (GC). However, the prognostic value of combination of C-reactive protein and PALB (CRP/PALB) remains unclear. Methods A total of 419 gastric cancer patients included in a clinical trial (NCT02327481) were analyzed. The present study is a substudy of the trial. Receiver operating characteristic (ROC) curves were generated, and by calculating the areas under the curve (AUC) and the C-index, the discriminative ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 48 publications
0
79
0
Order By: Relevance
“…The preoperative measurements of the complete blood counts (CBC), C-reactive protein (CRP) and albumin (ALB) were derived within the 7 days prior to surgery as stated previously [19]. All blood tests were performed using the same sample.…”
Section: Definitionsmentioning
confidence: 99%
“…The preoperative measurements of the complete blood counts (CBC), C-reactive protein (CRP) and albumin (ALB) were derived within the 7 days prior to surgery as stated previously [19]. All blood tests were performed using the same sample.…”
Section: Definitionsmentioning
confidence: 99%
“…6 To achieve precise individualized therapy in patients with HCC, the discovery of appropriate markers for proper prognostic evaluation is urgently needed. 11,12 Nevertheless, whether the CAR is linked to the prognosis in patients with HCC following TACE and RFA is unknown. 7 Recently, accumulating evidence has indicated that the systemic inflammatory response (SIR) is pivotal in tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…An increased CAR is related to an unfavorable prognosis of various cancers, for example, cervical cancer and esophageal cancer. 11,12 Nevertheless, whether the CAR is linked to the prognosis in patients with HCC following TACE and RFA is unknown. Therefore, our study examined the prognostic importance of combining the CAR and the NLR in patients with HCC following TACE and RFA.…”
Section: Introductionmentioning
confidence: 99%
“…CRP is not only a marker of inflammation, but also a significant predictor of many chronic diseases, such as cardiovascular disease and inflammatory related chronic diseases as well as cancer incidence and cancer survival, as shown in cohort studies . Elevated triglycerides and reduced high‐density lipoprotein (HDL) cholesterol are associated with metabolic syndrome and cardiovascular disease .…”
Section: Introductionmentioning
confidence: 99%
“…CRP is not only a marker of inflammation, but also a significant predictor of many chronic diseases, such as cardiovascular disease and inflammatory related chronic diseases [27][28][29][30][31] as well as cancer incidence 32 and cancer survival, as shown in cohort studies. 31,[33][34][35][36] Elevated triglycerides and reduced high-density lipoprotein (HDL) cholesterol are associated with metabolic syndrome and cardiovascular disease. 37,38 Therefore, it is important to investigate the associations between unprocessed red meat and CRP and lipid biomarkers in populations with different smoking status.…”
Section: Introductionmentioning
confidence: 99%